Effects of salvianolate on bone metabolism in glucocorticoid-treated lupus-prone B6.MRL-Faslpr/J mice - Liu Y; Cui Y; Zhang X; Gao X; Su Y; Xu B; Wu T; Chen W; Cui L (Dove Medical Press, 2016)
Yanzhi Liu,1,2 Yang Cui,3 Xiao Zhang,3 Xiang Gao,4 Yanjie Su,2 Bilian Xu,2 Tie Wu,2 Wenshuang Chen,2 Liao Cui1,2 1College of Traditional Chinese Medicine, Southern Medical University, Guangzhou City, 2Department of Pharmacology, Guangdong Key Laboratory for Research and Development of Natural Drugs, Guangdong Medical University, Zhanjiang, 3Department of Rheumatology, Guangdong Provincial People’s Hospital, Guangzhou, 4Stem Cell Research and Cellular Therapy Center, Affiliated Hospital of Guangdong Medical University, Zhanjiang, People’s Republic of China Aim: To investigate the bone-protective effects of salvianolate (Sal), a total polyphenol from Radix Salviae miltiorrhizae, on bone tissue in the spontaneous lupus-prone mouse model, B6.MRL-Faslpr/J, undergoing glucocorticoid (GC) treatment.Methods: Fifteen-week-old female B6.MRL-Faslpr/J mice were administered either a daily dose of saline (lupus group), prednisone 6 mg/kg (GC group), Sal 60 mg/kg (Sal group); or GC plus Sal (GC + Sal group) for a duration of 12 weeks. Age-matched female C57BL/6J wild-type (WT) mice were used for control. Micro-computed tomography assessments, bone histomorphometry analysis, bone biomechanical test, immunohistochemistry and immunoblotting analysis for bone markers, and renal histology analysis were performed to support our research endeavor.Results: Lupus mice developed a marked bone loss and deterioration of mechanical properties of bone due to an increase in bone resorption rather than suppression of bone formation. GC treatment strongly inhibited bone formation in lupus mice. Sal treatment significantly attenuated osteogenic inhibition, and also suppressed hyperactive bone resorption, which recovered the bone mass and mechanical properties of bone in both the untreated and GC-treated lupus mice.Conclusion: The data support further preclinical investigation of Sal as a potential therapeutic strategy for the treatment of systemic lupus erythematosus-related bone loss. Keywords: SLE, osteoporosis, bone, MRL, skeleton